(untitled) (Journal of Economic Research & Business Administration, 2018)
The competitive advantage of the company lies at the heart of its success in the market. Competitive advantage is the achievement of leadership in costs, the achievement of differentiation or the achievement of focus, this means that the company intends to become the best. Competitive advantages are usually reduced to one of two basic advantages, this is the superiority in resources and positional superiority. Thus, competitive advantage is defined as a significant competitive advantage over cost-sharing, the results of which depend on the positioning strategy. The competitive war continues constantly, therefore there is no guarantee that competitive advantages will be maintained for a long time. In this regard, understanding sources of sustainable competitive advantages has become an important area of research in the field of marketing management. The article reveals the essence and need for the formation of competitive advantages. The article also analyzes the concept of competitive advantage. Having studied the relevant literature and analyzing the articles of other scientists, the author emphasizes the need and development of marketing management of competitive advantages. The author offers theoretical models of competitive advantages, made based on models of other authors, which will be useful in developing strategies within the framework of targeted assistance to companies. It is important for companies to regularly monitor and analyze strategies of target competitors in order to respond quickly to their actions, understand how to get ahead of them and always be in high positions in order to survive and conquer the market.